Staphylococcal toxic shock toxin specifically binds to cultured human epithelial cells and is rapidly internalized. - Kushnaryov, V M (1984)
Staphylococcal toxic shock syndrome toxin (TST) was labeled with 125I under mild conditions without apparent destruction of the molecule. [125I]TST bound specifically to human epithelial (Chang) cells in culture; the binding was inhibited by a 100-fold excess of unlabeled toxin. Scatchard analysis of the binding data indicated about 10(4) receptor sites per cell and a dissociation constant (Kd) of 4 X 10(-9) M. When cells pretreated with TST at 4 degrees C were swiftly transferred to 37 degrees C, the amount of surface-bound toxin rapidly declined, as determined by release of noninternalized label from the cell surface. Half-time (t1/2) of internalization was about 1.5 min. Ultrastructural studies showed that toxin labeled with ferritin-conjugated antibodies entered the cytoplasm via coated pits forming coated vesicles in the first 2 min of incubation at 37 degrees C. The coated vesicles coalesced with transport vesicles that are ultrastructurally unlike receptosomes. Thus, the unusual ultrastructural pattern of this internalization suggests that TST is initially internalized by receptor-mediated endocytosis and then enters an alternate pathway involving translocation in special transport vesicles, perhaps to other cells.